SNHG12: An LncRNA as a Potential Therapeutic Target and Biomarker for Human Cancer - Tamang, Suraksha; Acharya, Varnali; Roy, Deepronil; Sharma, Rinka; Aryaa, Apeksha; Sharma, Uttam; Khandelwal, Akanksha; Prakash, Hridayesh; Vasquez, Karen M.; Jain, Aklank (Frontiers in Oncology, 2019)
Limitations in current diagnostic procedures warrant identification of new methodologies to improve diagnoses of cancer patients. In this context, long non-coding RNAs (lncRNAs) have emerged as stable biomarkers which are expressed abundantly in tumors. Importantly, these can be detected at all stages of tumor development, and thus may provide potential biomarkers and/or therapeutic targets. Recently, we suggested that aberrant levels of lncRNAs can be used to determine the invasive and metastatic potential of tumor cells. Further, direct correlations of lncRNAs with cancer-derived inflammation, metastasis, epithelial-to-mesenchymal transition, and other hallmarks of cancer indicate their potential as biomarkers and targets for cancer. Thus, in this review we have discussed the importance of small nucleolar RNA host gene 12 (SNHG12), a lncRNA, as a potential biomarker for a variety of cancers. A meta-analysis of a large cohort of cancer patients revealed that SNHG12 may also serve as a potential target for cancer-directed interventions due to its involvement in unfolded protein responses, which many tumor cells exploit to both evade immune-mediated attack and enhance the polarization of effector immune cells (e.g., macrophages and T cells). Thus, we propose that SNHG12 may serve as both a biomarker and a druggable therapeutic target with promising clinical potential.